Stakeholder perceptions of the safety and assurance of artificial intelligence in healthcare. (November 2022) - Sujan, Mark A.; White, Sean; Habli, Ibrahim; Reynolds, Nick
Highlights: Qualitative study of stakeholder perceptions of healthcare AI. Diversity of views can support responsible innovation. There is a need for a systems approach to AI safety. The impact on patient – clinician relationship needs consideration. Ethical, legal and societal aspects need to be addressed. Abstract: Introduction: There is an increasing number of healthcare AI applications in development or already in use. However, the safety impact of using AI in healthcare is largely unknown. In this paper we explore how different stakeholders (patients, hospital staff, technology developers, regulators) think about safety and safety assurance of healthcare AI. Methods: 26 interviews were undertaken with patients, hospital staff, technology developers and regulators to explore their perceptions on the safety and the safety assurance of AI in healthcare using the example of an AI-based infusion pump in the intensive care unit. Data were analysed using thematic analysis. Results: Participant perceptions related to: the potential impact of healthcare AI, requirements for human-AI interaction, safety assurance practices and regulatory frameworks for AI and the gaps that exist, and how incidents involving AI should be managed. Conclusion: The description of a diversity of views can support responsible innovation and adoption of such technologies in healthcare. Safety and assurance of healthcare AI need to be based on a systems approach that expands the current technology-centric focus. Lessons can be learned from the experiences with highly automated systems across safety-critical industries, but issues such as the impact of AI on the relationship between patients and their clinicians require greater consideration. Existing standards and best practices for the design and assurance of systems should be followed, but there is a need for greater awareness of these among technology developers. In addition, wider ethical, legal, and societal implications of the use of AI in healthcare need to be addressed.